Statistical Analysis of Extreme Rainfall Trends Events over Savanna Zones of Nigeria and its Possible Impacts (The Proceedings of The International Conference on Climate Change, 2020)
This study analysed the trends in extreme rainfall of fourteen (14) synoptic stations in the savanna zones of Nigeria for the period of 35 years (1981-2015). The study acquired daily rainfall data from Environmental Management Programmed, Federal University of Technology Minna. The data was categories into seven extreme indices (heavy, very heavy, extremely heavy rainfall days, 1-day annual maximum rainfall amount, five 5-days annual maximum rainfall amount, Consecutive wet days, and simple daily intensity index) by using ETCCDI indices through RClimDex software. Statistical tests of Mann-Kendall (MK), based on a non-parametric approach was use to evaluate the possible trend in the derived indices. Results showed significant and insignificant mixed trends of increasing and decreasing in the seven selected extreme indices across the study areas. Three stations (Bauchi, Kano, and Katsina) in Sudano-Sahelian savanna zones showed consistent significant increasing trends in most of the extreme indices while two stations (Abuja and Yola) showed consistent decreasing trends in most of the extreme indices. Generally, the results showed an increase in the occurrence of extreme rainfall events in the selected variables. The increase trends are possible pointer to climate change and a possible influencing factor to the frequent occurrence of flooding across the study areas.
Keywords: Rainfall; Extreme; Mann-Kendall; Savanna; Nigeria